Bioanalytical strategies in drug discovery and development. (3rd July 2021) - Thakur, Aarzoo; Tan, Zhiyuan; Kameyama, Tsubasa; El-Khateeb, Eman; Nagpal, Shakti; Malone, Stephanie; Jamwal, Rohitash; Nwabufo, Chukwunonso K.
Abstract: A reliable, rapid, and effective bioanalytical method is essential for the determination of the pharmacokinetic, pharmacodynamic, and toxicokinetic parameters that inform the safety and efficacy profile of investigational drugs. The overall goal of bioanalytical method development is to elucidate the procedure and operating conditions under which a method can sufficiently extract, qualify, and/or quantify the analyte(s) of interest and/or their metabolites for the intended purpose. Given the difference in the physicochemical properties of small and large molecule drugs, different strategies need to be adopted for the development of an effective and efficient bioanalytical method. Herein, we provide an overview of different sample preparation strategies, analytical platforms, as well as procedures for achieving high throughput for bioanalysis of small and large molecule drugs.